Nitrogen-doped carbon nanotubes with mosaic iron-cobalt oxide coated iron-cobalt alloy heterogeneous particles, preparation method and application thereof
Patent Information
- Application Number
- CN202310111200.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-02-10
AI Technical Summary
[0006]基于此,有必要针对如何提升催化性能的问题,提供一种镶嵌铁钴氧化物包覆铁钴合金异质颗粒的氮掺杂碳纳米管及其制备方法和应用
[0024](1)具有较大的比表面积,分级孔结构,丰富高效的活性位点以及较强的表面氧吸附能力;
Smart Images

Figure CN116230964B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of zinc-air battery catalyst technology, and in particular to a nitrogen-doped carbon nanotube with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles embedded in it, its preparation method, and its application. Background Technology
[0002] With severe fossil fuel pollution and dwindling petrochemical resources worldwide, the vigorous development of sustainable energy is an urgent priority, making advanced energy storage and conversion equipment essential. This necessitates research into efficient and environmentally friendly energy storage and conversion technologies. Since the late 20th century, increasing attention has been paid to energy materials and related devices, particularly in the field of electrochemistry. Currently, one of the most representative research topics is the metal-air battery (MAB), a device that can effectively improve energy systems and possesses significant development potential.
[0003] Metal-air batteries are diverse, using air as the cathode material and metal anodes such as magnesium, aluminum, zinc, or iron. Among them, zinc-air batteries (ZABs) possess a relatively high theoretical specific energy (1370 Wh·kg⁻¹). -1 Zinc-air batteries are among the most promising metal-air batteries, and researchers have conducted extensive studies on them over the past 20 years, widely applying them in the new energy field. Rechargeable zinc-air batteries can be recharged after discharge, achieving cyclic use. The battery's working principle is as follows: during discharge, an external electrical appliance is connected, and the air cathode undergoes the oxygen reduction reaction (ORR), with a total reaction standard potential of 1.65V. When the battery is charged, an external power source is connected, and the air cathode undergoes the oxygen evolution reaction (OER). Zinc-air batteries have high energy density, and their raw material, zinc, is inexpensive and environmentally friendly. However, the kinetics of the two half-reactions at the air cathode, ORR and OER, are slow, leading to low efficiency in zinc-air batteries. Therefore, it is necessary to develop efficient ORR and OER catalysts to improve the reaction rate, thereby advancing zinc-air battery technology.
[0004] Currently, noble metal-based materials such as platinum-carbon (Pt-C), iridium oxide (IrO2), and ruthenium oxide (RuO2) can serve as highly efficient catalysts for zinc-air batteries. However, their poor stability, coupled with the high price and scarcity of precious metals, prevents the commercialization of zinc-air batteries and similar devices.
[0005] Currently, transition metal-based materials have been reported to exhibit good electrocatalytic activity and durability. Raw materials for transition metals such as nickel (Ni), iron (Fe), and cobalt (Co) are abundant and inexpensive. Porous carbon materials possess good electrical conductivity and mass transfer efficiency. Doping with heteroatoms such as nitrogen (N), sulfur (S), phosphorus (P), and selenium (Se) can enhance the conductivity and ORR catalytic activity of carbon through mechanisms such as defect generation. Therefore, transition metal (Ni, Fe, Co, etc.) co-doped carbon materials with nitrogen are among the most promising oxygen electrocatalysts. However, transition metal nanomaterials are prone to aggregation under electrochemical action and leaching from carbon materials, leading to a significant reduction in the reactivity of the composite carbon materials and thus lowering their catalytic performance. Summary of the Invention
[0006] Therefore, it is necessary to address the issue of how to improve catalytic performance by providing a method for preparing nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles and their applications.
[0007] A method for preparing nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles includes the following steps:
[0008] The carbon-nitrogen source, iron transition metal salt, and solvent are mixed evenly to obtain the first mixed solution;
[0009] A cobalt transition metal salt solution was added dropwise to the first mixed solution, and after sufficient reaction, a second mixed solution was obtained.
[0010] The second mixed solution is mixed evenly with the aqueous solution of graphene oxide, and after the reaction is complete, solid-liquid separation is performed and the solids are retained.
[0011] The solid was calcined at 300°C–500°C under an inert or reducing atmosphere. After complete reaction, the temperature was raised to 700°C–1000°C and calcined again. After complete reaction, the temperature was lowered to room temperature to remove impurities, yielding nitrogen-doped carbon nanotubes embedded with iron-cobalt alloy particles.
[0012] In an oxygen-containing atmosphere, the nitrogen-doped carbon nanotubes embedded with iron-cobalt alloy particles are heated to 160°C to 420°C for calcination. After the reaction is complete, the temperature is lowered to room temperature to obtain nitrogen-doped carbon nanotubes embedded with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles.
[0013] The method for preparing nitrogen-doped carbon nanotubes with iron-cobalt alloy heteroparticles embedded with iron-cobalt oxide according to the technical solution of this invention involves first generating an iron-cobalt alloy under an inert or reducing atmosphere, followed by the generation of nitrogen-doped carbon nanotubes. This allows the iron-cobalt alloy nanoparticles to be embedded in the framework of the nitrogen-doped carbon nanotubes, thereby avoiding the aggregation of the iron-cobalt alloy nanoparticles and facilitating electron transport. This results in nitrogen-doped carbon nanotubes with iron-cobalt oxide embedded with iron-cobalt alloy heteroparticles exhibiting excellent ORR and OER bifunctional catalytic performance. Simultaneously, the reaction under an oxygen-containing atmosphere generates an iron-cobalt oxide coating layer on the surface of the iron-cobalt alloy, which not only prevents undesirable oxidation of the iron-cobalt alloy during the catalytic reaction but also enables the nitrogen-doped carbon nanotubes with iron-cobalt oxide embedded with iron-cobalt alloy heteroparticles to exhibit highly efficient and stable ORR and OER catalytic performance.
[0014] In one feasible implementation, the ratio of the amount of carbon and nitrogen source, the amount of iron in the iron transition metal salt, the amount of cobalt in the cobalt transition metal salt solution, to the mass of graphene in the graphene oxide aqueous solution is (5 mmol to 50 mmol): (0.5 mmol to 20 mol): (0.5 mmol to 25 mmol): (25 mg to 100 mg).
[0015] In one feasible implementation, the carbon and nitrogen source is selected from at least one of melamine, dicyandiamide, polyaniline, and urea.
[0016] In one feasible implementation, the iron transition metal salt is selected from at least one of K3[Fe(CN)6], Fe(NO3)3·6H2O, FeCl3·6H2O, Fe(CH3COO)3 and Fe2(SO4)3·6H2O.
[0017] In one feasible implementation, the concentration of the cobalt transition metal salt solution is 0.3 mol / L to 1 mol / L; and / or
[0018] The cobalt transition metal salt in the cobalt transition metal salt solution is selected from at least one of Co(NO3)2·6H2O, CoCl2·6H2O, Co(CH3COO)2, CoCl2, CoSO4·7H2O, and CoSO4·H2O.
[0019] In one feasible implementation, the concentration of the graphene oxide aqueous solution is 0.5 g / L to 2 g / L.
[0020] In one feasible implementation, the impurity removal operation is performed by cleaning with a 0.1M to 0.5M hydrochloric acid solution.
[0021] In one feasible implementation, the inert atmosphere is N2 or Ar, the reducing atmosphere is a mixture of N2 and H2 or a mixture of Ar and H2, and the oxygen-containing atmosphere is air.
[0022] A nitrogen-doped carbon nanotube with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles is prepared by any of the above-mentioned methods for preparing nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles.
[0023] The nitrogen-doped carbon nanotubes of the present invention, which are embedded with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles, have the following advantages:
[0024] (1) It has a large specific surface area, hierarchical pore structure, abundant and efficient active sites and strong surface oxygen adsorption capacity.
[0025] (2) It not only prevents the electrolyte from directly corroding the alloy nanoparticles, thus maintaining their high ORR cycle stability, but also helps to improve their resistance to methanol interference and CO poisoning.
[0026] (3) It has a core-shell structure with a stable iron-cobalt oxide layer coating the iron-cobalt alloy nanoparticles, which not only prevents iron and cobalt from undergoing adverse oxidation in the catalytic reaction, but also exhibits efficient and stable ORR / OER electrocatalytic performance in the reaction.
[0027] The application of nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles as catalysts in zinc-air batteries.
[0028] The nitrogen-doped carbon nanotubes embedded with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles serve as bifunctional catalysts for zinc-air batteries. They are used to catalyze ORR and OER reactions in zinc-air batteries without affecting electron transport, providing more catalytic active sites, and allowing the electrocatalytic activity of the iron-cobalt alloy to be fully exhibited in the reaction. They have good bifunctional catalytic performance for both ORR and OER. Attached Figure Description
[0029] Figure 1 This is a flowchart of a method for preparing nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles according to an embodiment of the present invention.
[0030] Figure 2 The image shows the microstructure of nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles in Example 1 under a scanning electron microscope (SEM).
[0031] Figure 3 Linear sweep voltammetric curves (LSV) of the oxygen reduction reaction (ORR) of the catalysts of Example 1 and Comparative Example 1 in O2-saturated 0.1M KOH solution are shown.
[0032] Figure 4 Linear sweep voltammetry (LSV) curves of the oxygen evolution reaction (OER) of the catalysts in Example 1 and Comparative Example 1 in 0.1 M KOH solution.
[0033] Figure 5 Linear sweep voltammetric curves (LSV) of the oxygen reduction reaction (ORR) of the catalysts in Examples 1-3 in O2-saturated 0.1M KOH solution are shown.
[0034] Figure 6 Linear sweep voltammetry (LSV) curves of the oxygen evolution reaction (OER) of the catalysts in Examples 1-3 in 0.1M KOH solution. Detailed Implementation
[0035] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Many specific details are set forth in the following description to provide a thorough understanding of the present invention. However, the present invention can be practiced in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0037] Please see Figure 1 The method for preparing nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles according to one embodiment of the present invention includes the following steps:
[0038] S10. Mix the carbon-nitrogen source, iron transition metal salt and solvent evenly to obtain the first mixed solution.
[0039] The order in which the carbon-nitrogen source, the iron transition metal salt, and the solvent are mixed is not limited. The carbon-nitrogen source and the iron transition metal salt can be dissolved separately in a portion of the solvent and then mixed; the carbon-nitrogen source and the iron transition metal salt can be dissolved together in the solvent and then mixed; or one of the carbon-nitrogen source and the iron transition metal salt can be dissolved in a portion of the solvent and then the other of the carbon-nitrogen source and the iron transition metal salt can be added and mixed.
[0040] Water is the preferred solvent. The carbon and nitrogen sources, iron transition metal salts, and subsequent raw materials have high solubility in water and dissolve quickly, which helps ensure efficient reaction.
[0041] In one feasible implementation, the carbon and nitrogen source is selected from at least one of melamine, dicyandiamide, polyaniline, and urea.
[0042] In one feasible implementation, the iron transition metal salt is selected from at least one of K3[Fe(CN)6], Fe(NO3)3·6H2O, FeCl3·6H2O, Fe(CH3COO)3 and Fe2(SO4)3·6H2O.
[0043] In one feasible implementation, the operation of uniformly mixing the carbon-nitrogen source, the iron transition metal salt, and the solvent is as follows: dissolve the carbon-nitrogen source in deionized water at room temperature, then mix the 0.1M to 0.5M iron transition metal salt aqueous solution with the carbon-nitrogen source solution and stir for 1 to 10 hours.
[0044] S20. Add the cobalt transition metal salt solution dropwise to the first mixed solution obtained in step S10, and after the reaction is complete, obtain the second mixed solution.
[0045] The purpose of adding the cobalt transition metal salt solution dropwise is to prevent the reaction from being too vigorous and causing particle agglomeration. The optimal reaction time is 2 to 20 hours.
[0046] In one feasible implementation, the concentration of the cobalt transition metal salt solution is 0.3 mol / L to 1 mol / L.
[0047] In one feasible implementation, the cobalt transition metal salt in the cobalt transition metal salt solution is selected from at least one of Co(NO3)2·6H2O, CoCl2·6H2O, Co(CH3COO)2, CoCl2, CoSO4·7H2O, and CoSO4·H2O.
[0048] In step S20, when the carbon and nitrogen source is melamine, the iron transition metal salt is K3[Fe(CN)6], and the cobalt transition metal salt is CoCl2·6H2O or CoCl2, the Prussian blue analog (PBA)-melamine precursor is generated after the reaction is complete.
[0049] S30. The second mixed solution obtained in step S20 is mixed evenly with the aqueous solution of graphene oxide. After the reaction is complete, solid-liquid separation is performed and the solid is retained.
[0050] Solid-liquid separation includes, for example, vacuum filtration or other solid-liquid separation methods.
[0051] In one feasible implementation, the concentration of the aqueous graphene oxide (GO) solution is 0.5 g / L to 2 g / L.
[0052] In one feasible implementation, the ratio of the amount of carbon and nitrogen source, the amount of iron in the iron transition metal salt, the amount of cobalt in the cobalt transition metal salt solution, to the mass of graphene in the graphene oxide aqueous solution is (5 mmol–50 mmol): (0.5 mmol–20 mol): (0.5 mmol–25 mmol): (25 mg–100 mg).
[0053] In step S30, when the carbon and nitrogen source is melamine, the iron transition metal salt is K3[Fe(CN)6], and the cobalt transition metal salt is CoCl2·6H2O or CoCl2, the Prussian blue analog (PBA)-melamine precursor reacts fully with graphene oxide to generate PBA-melamine-GO solid. It can then be further dried at 40℃~80℃ for 10h~20h.
[0054] S40. Under an inert or reducing atmosphere, the solid obtained in step S30 is calcined at a temperature of 300℃ to 500℃. After the reaction is complete, the temperature is raised to 700℃ to 1000℃ and calcined again. After the reaction is complete, the temperature is lowered to room temperature to remove impurities and obtain nitrogen-doped carbon nanotubes embedded with iron-cobalt alloy particles.
[0055] In step S40, calcination of the solid at 300℃ to 500℃ generates an iron-cobalt alloy, while melamine vaporizes and deposits at the bottom of the equipment at this temperature. Subsequent calcination at 700℃ to 1000℃ generates nitrogen-doped carbon nanotubes (NCNTs) embedded with iron-cobalt alloy particles. This avoids the agglomeration of the iron-cobalt alloy nanoparticles, facilitates electron transport, and gives the nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles excellent bifunctional catalytic performance for both ORR and OER.
[0056] In one feasible implementation, the solid is placed in a high-temperature tube furnace and calcined at 300℃ to 500℃ for 1h to 6h under an inert or reducing atmosphere at a heating rate of 1℃ / min to 5℃ / min, and then calcined at 700℃ to 1000℃ for another 1h to 5h, and then cooled to room temperature.
[0057] In one feasible implementation, the inert atmosphere is N2 or Ar, and the reducing atmosphere is a mixture of N2 and H2 or a mixture of Ar and H2.
[0058] In one feasible implementation, the impurity removal process involves cleaning with a 0.1M to 0.5M hydrochloric acid solution. This removes residual metals and other impurities that are not embedded in carbon nanotubes.
[0059] S50. Under an oxygen-containing atmosphere, the nitrogen-doped carbon nanotubes embedded with iron-cobalt alloy particles obtained in step S40 are heated to 160℃~420℃ for calcination. After the reaction is complete, the temperature is lowered to room temperature to obtain nitrogen-doped carbon nanotubes embedded with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles.
[0060] In one feasible implementation, the oxygen-containing atmosphere is air.
[0061] In one feasible implementation, the heating rate is 5℃ / min to 10℃ / min.
[0062] In step S50, the reaction under an oxygen-containing atmosphere can generate an iron-cobalt oxide coating layer on the surface of the iron-cobalt alloy. This not only prevents the iron-cobalt alloy from undergoing adverse oxidation during the catalytic reaction, but also enables the nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles to exhibit efficient and stable ORR and OER catalytic performance.
[0063] The method for preparing nitrogen-doped carbon nanotubes with iron-cobalt alloy heteroparticles embedded with iron-cobalt oxide according to the technical solution of this invention involves first generating an iron-cobalt alloy under an inert or reducing atmosphere, followed by the generation of nitrogen-doped carbon nanotubes. This allows the iron-cobalt alloy nanoparticles to be embedded in the framework of the nitrogen-doped carbon nanotubes, thereby avoiding the aggregation of the iron-cobalt alloy nanoparticles and facilitating electron transport. This results in nitrogen-doped carbon nanotubes with iron-cobalt oxide embedded with iron-cobalt alloy heteroparticles exhibiting excellent ORR and OER bifunctional catalytic performance. Simultaneously, the reaction under an oxygen-containing atmosphere generates an iron-cobalt oxide coating layer on the surface of the iron-cobalt alloy, which not only prevents undesirable oxidation of the iron-cobalt alloy during the catalytic reaction but also enables the nitrogen-doped carbon nanotubes with iron-cobalt oxide embedded with iron-cobalt alloy heteroparticles to exhibit highly efficient and stable ORR and OER catalytic performance.
[0064] One embodiment of the nitrogen-doped carbon nanotubes embedded with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles is prepared by any of the above-described methods for preparing nitrogen-doped carbon nanotubes embedded with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles.
[0065] In the nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles, the structural unit is a conductive network with nitrogen-doped carbon nanotubes (NCNTs), and the iron-cobalt alloy nanoparticles inside the carbon nanotubes are partially thermally oxidized to form metal@metal oxide heteroparticles.
[0066] The nitrogen-doped carbon nanotubes of the present invention, which are embedded with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles, have the following advantages:
[0067] (1) It has a large specific surface area, hierarchical pore structure, abundant and efficient active sites and strong surface oxygen adsorption capacity.
[0068] (2) It not only prevents the electrolyte from directly corroding the alloy nanoparticles, thus maintaining their high ORR cycle stability, but also helps to improve their resistance to methanol interference and CO poisoning.
[0069] (3) It has a core-shell structure with a stable iron-cobalt oxide layer coating the iron-cobalt alloy nanoparticles, which not only prevents iron and cobalt from undergoing adverse oxidation in the catalytic reaction, but also exhibits efficient and stable ORR / OER electrocatalytic performance in the reaction.
[0070] One embodiment describes the application of nitrogen-doped carbon nanotubes embedded with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles as a catalyst in zinc-air batteries.
[0071] The nitrogen-doped carbon nanotubes embedded with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles serve as bifunctional catalysts for zinc-air batteries. They are used to catalyze ORR and OER reactions in zinc-air batteries without affecting electron transport, providing more catalytic active sites, and allowing the electrocatalytic activity of the iron-cobalt alloy to be fully exhibited in the reaction. They have good bifunctional catalytic performance for both ORR and OER.
[0072] Referring to the above implementation details, in order to make the technical solution of this application more specific, clear, and easy to understand, examples of the technical solution of this application are given below. However, it should be noted that the content to be protected by this application is not limited to the following embodiments.
[0073] Example 1
[0074] 10 mmol of melamine was dissolved in 20 mL of deionized water at room temperature. Then, 12 mL of 0.1 M potassium ferricyanide {K3[Fe(CN)6]} aqueous solution was mixed with the melamine solution and stirred for 5 h to obtain the first mixed solution.
[0075] Then, under vigorous stirring, 10 mL of an aqueous solution containing 3 mmol of cobalt chloride (CoCl2) was added dropwise to the first mixed solution above, and stirring was continued for 12 h to form Prussian blue analog (PBA)-melamine precursor, thus obtaining the second mixed solution;
[0076] Next, 20 mL of GO aqueous solution containing 30 mg of graphene oxide (GO) was added to the second mixed solution above, and the mixture was stirred for 20 h. PBA-melamine-GO solid was obtained by filtration and dried at 70 °C for 14 h.
[0077] The obtained PBA-melamine-GO solid was placed in a high-temperature tube furnace and heated at 4°C / min under an inert or reducing atmosphere. -1 The heating rate was increased to 400℃ and calcined for 1 hour, then increased at 2℃·min. -1 The heating rate was increased to 800℃, and calcination was continued for 3 hours. After that, the temperature was reduced to room temperature, and the mixture was cleaned with 0.2M HCl to remove metal residues and impurities that were not embedded in carbon nanotubes, thus obtaining a nitrogen-doped carbon nanotube (NCNT) composite material (FeCo / NCNT) with embedded FeCo alloy particles.
[0078] Take an appropriate amount of the above FeCo / NCNT powder and place it in a corundum porcelain boat, spreading it evenly. Place the porcelain boat in a muffle furnace and heat it at 7°C·min in an air atmosphere. -1 The heating rate was increased to 400℃ and calcined for 4 hours. After cooling to room temperature, a nitrogen-doped carbon nanotube bifunctional catalyst (FeCo@FeCoO / NCNT) was obtained, which was embedded with iron cobalt oxide-coated iron cobalt alloy heteroparticles.
[0079] The FeCo@FeCoO / NCNT prepared in Example 1 was characterized by scanning electron microscopy, and the results were obtained. Figure 2 .Depend on Figure 2 It can be seen that the carbon nanotubes in FeCo@FeCoO / NCNT prepared in Example 1 have a small diameter and are rich in CNTs, with metal nanoparticles embedded in the CNTs.
[0080] Example 2
[0081] 29 mmol of melamine was dissolved in 26 mL of deionized water at room temperature. Then, 21 mL of 0.2 M potassium ferricyanide {K3[Fe(CN)6]} aqueous solution was mixed with the melamine solution and stirred for 10 h to obtain the first mixed solution.
[0082] Next, 17 mL of an aqueous solution containing 7 mmol of cobalt chloride (CoCl2) was added dropwise to the first mixed solution under vigorous stirring, and then stirring was continued for 20 h to form a Prussian blue analog (PBA)-melamine precursor, thus obtaining the second mixed solution;
[0083] Next, 30 mL of GO aqueous solution containing 60 mg of graphene oxide (GO) was added to the second mixed solution above, and the mixture was stirred for 20 h. PBA-melamine-GO solid was obtained by filtration and dried at 65 °C for 19 h.
[0084] The obtained PBA-melamine-GO solid was placed in a high-temperature tube furnace and heated at 3.5 °C / min under an inert or reducing atmosphere. -1 The heating rate was increased to 370℃ and calcined for 1.5 hours, then increased at 3℃·min. -1The heating rate was increased to 850℃, and calcination was continued for 4 hours. After that, the temperature was reduced to room temperature, and the mixture was cleaned with 0.4M HCl to remove metal residues and impurities that were not embedded in carbon nanotubes, thus obtaining a nitrogen-doped carbon nanotube (NCNT) composite material (FeCo / NCNT) with embedded FeCo alloy particles.
[0085] Take an appropriate amount of the above FeCo / NCNT powder and place it in a corundum porcelain boat, spreading it evenly. Place the porcelain boat in a muffle furnace and heat it at 9°C·min in an air atmosphere. -1 The heating rate was increased to 380℃ and calcined for 3.5h. After cooling to room temperature, a nitrogen-doped carbon nanotube bifunctional catalyst (FeCo@FeCoO / NCNT-2) was obtained, which was embedded with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles.
[0086] Example 3
[0087] 35 mmol of melamine was dissolved in 50 mL of deionized water at room temperature. Then, 40 mL of 0.45 M potassium ferricyanide {K3[Fe(CN)6]} aqueous solution was mixed with the melamine solution and stirred for 23 h to obtain the first mixed solution.
[0088] Next, 28 mL of an aqueous solution containing 23 mmol of cobalt chloride (CoCl2) was added dropwise to the first mixed solution under vigorous stirring, and then stirring was continued for 35 h to form Prussian blue analog (PBA)-melamine precursor, thus obtaining the second mixed solution;
[0089] Next, 60 mL of GO aqueous solution containing 78 mg of graphene oxide (GO) was added to the second mixed solution above, and stirring was continued for 28 h. PBA-melamine-GO solid was obtained by suction filtration and dried at 78 °C for 26 h.
[0090] The obtained PBA-melamine-GO solid was placed in a high-temperature tube furnace and heated at 5°C / min under an inert or reducing atmosphere. -1 The heating rate was increased to 430℃ and calcined for 3 hours, then increased at 5℃·min. -1 The heating rate was increased to 900℃, and calcination was continued for 5 hours. After that, the temperature was reduced to room temperature, and the mixture was cleaned with 0.3M HCl to remove metal residues and impurities that were not embedded in carbon nanotubes, thus obtaining a nitrogen-doped carbon nanotube (NCNT) composite material (FeCo / NCNT) with embedded FeCo alloy particles.
[0091] Take an appropriate amount of the above FeCo / NCNT powder and place it in a corundum porcelain boat, spreading it evenly. Place the porcelain boat in a muffle furnace and heat it at 10℃·min under an air atmosphere. -1The heating rate was increased to 450℃ and calcined for 5 hours. After cooling to room temperature, a nitrogen-doped carbon nanotube bifunctional catalyst (FeCo@FeCoO / NCNT-3) was obtained, which was embedded with iron cobalt oxide-coated iron cobalt alloy heteroparticles.
[0092] Comparative Example 1
[0093] This comparative example is the same as Example 1, providing a nitrogen-doped carbon nanotube (FeCo@NCNT) embedded with FeCo alloy particles and its preparation method, the steps of which are as follows:
[0094] 10 mmol of melamine was dissolved in 20 mL of deionized water at room temperature. Then, 12 mL of 0.1 M potassium ferricyanide {K3[Fe(CN)6]} aqueous solution was mixed with the melamine solution and stirred for 5 h to obtain the first mixed solution.
[0095] Then, under vigorous stirring, 10 mL of an aqueous solution containing 3 mmol of cobalt chloride (CoCl2) was added dropwise to the first mixed solution above, and stirring was continued for 12 h to form Prussian blue analog (PBA)-melamine precursor, thus obtaining the second mixed solution;
[0096] Next, 20 mL of GO aqueous solution containing 30 mg of graphene oxide (GO) was added to the second mixed solution above, and the mixture was stirred for 20 h. PBA-melamine-GO solid was obtained by filtration and dried at 70 °C for 14 h.
[0097] The obtained PBA-melamine-GO solid was placed in a high-temperature tube furnace and heated at 4°C / min under an inert or reducing atmosphere. -1 The heating rate was increased to 400℃ and calcined for 1 hour, then increased at 2℃·min. -1 The heating rate was increased to 800℃, and calcination was continued for 3 hours. After that, the temperature was lowered to room temperature, and the mixture was cleaned with 0.2M HCl to remove metal residues and impurities that were not embedded in carbon nanotubes, thus obtaining the nitrogen-doped carbon nanotube (NCNT) composite material (FeCo / NCNT) with embedded FeCo alloy particles as shown in Comparative Example 1.
[0098] Performance testing:
[0099] Bifunctional catalytic performance evaluation:
[0100] All electrochemical tests were conducted using a CHI 760E electrochemical workstation equipped with a PINE rotating disk electrode testing system, and all electrochemical tests were performed at room temperature.
[0101] (1) Preparation of the working electrode: Before using the rotating disk electrode (RDE), i.e., the glassy carbon electrode (GC, d = 5 mm), the electrode surface was first polished to a mirror finish on a polishing cloth using Al2O3 powder, then rinsed several times with deionized water, and dried at room temperature for later use. 4 mg of the FeCo@FeCoO / NCNT material obtained in Example 1 and the FeCo / NCNT material obtained in Comparative Example 1, 261 μL of isopropanol, 652 μL of deionized water, and 87 μL of Nafion solution (5 wt.%) were accurately weighed and mixed. The mixture was ultrasonically treated for 1 h. Finally, 10 μL of the prepared slurry was uniformly drop-coated onto the GCE surface and allowed to dry naturally to obtain the working electrode for testing. The catalyst loading on the electrode surface was approximately 0.20 mg·cm³. -2 As a control experiment, commercial 20 wt.% Pt / C catalyst and RuO2 catalyst were also prepared and tested using the same electrode preparation method.
[0102] (2) Electrochemical performance test: A standard three-electrode electrochemical test system was used in the test process, in which the counter electrode was a Pt sheet, the reference electrode was a saturated calomel electrode (SCE) and the working electrode prepared above.
[0103] The ORR performance of the nitrogen-doped carbon nanotube bifunctional catalysts obtained in Examples 1-3 and the FeCo / NCNT material obtained in Comparative Example 1 were tested using a rotating disk electrode (RDE) in O2-saturated 0.1M KOH solution and OER performance in 0.1M KOH solution without O2. LSV curves were obtained at a rotation speed of 1600 rpm. The results are as follows: Figures 3-6 As shown.
[0104] from Figure 3 As can be seen, compared with the FeCo / NCNT material obtained in Comparative Example 1, the FeCo@FeCoO / NCNT material obtained in Example 1 exhibits high ORR electrocatalytic activity, with an onset potential of 0.871 V vs. RHE and a half-wave potential of 0.805 V vs. RHE in alkaline medium. Figure 4 As can be seen, compared with the FeCo / NCNT material obtained in Comparative Example 1, the FeCo@FeCoO / NCNT material obtained in Example 1 also exhibits high OER electrocatalytic activity, with the current density reaching 10 mA·cm⁻¹. -2 At that time, an overpotential of 345mV was observed in the alkaline medium. From Figure 5 It can be seen that the nitrogen-doped carbon nanotube bifunctional catalysts obtained in Examples 1-3 all exhibit high ORR electrocatalytic activity. Figure 6It can be seen that the nitrogen-doped carbon nanotube bifunctional catalysts obtained in Examples 1-3 all exhibit high OER electrocatalytic activity. Overall, the above indicates that the preparation method of nitrogen-doped carbon nanotubes with iron-cobalt alloy heteroparticles embedded in iron-cobalt oxide using the technical solution of this invention can improve their catalytic performance when used as a catalyst in zinc-air batteries.
[0105] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0106] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles, characterized in that, Includes the following steps: A carbon-nitrogen source, an iron transition metal salt, and a solvent are mixed evenly to obtain a first mixed solution; the carbon-nitrogen source is melamine, and the iron transition metal salt is K3[Fe(CN)6]. A cobalt transition metal salt solution is added dropwise to the first mixed solution, and after sufficient reaction, a second mixed solution is obtained; the cobalt transition metal salt is CoCl2·6H2O or CoCl2; The second mixed solution was mixed evenly with the graphene oxide aqueous solution, and after the reaction was complete, solid-liquid separation was performed and the Prussian blue analogue-melamine-graphene oxide solid was retained. The solid is calcined at 300°C to 500°C under an inert or reducing atmosphere. After sufficient reaction, the temperature is raised to 700°C to 1000°C and calcined again. After sufficient reaction, the temperature is lowered to room temperature to remove impurities, yielding nitrogen-doped carbon nanotubes embedded with iron-cobalt alloy particles, wherein the iron-cobalt alloy nanoparticles are embedded in the framework of the nitrogen-doped carbon nanotubes; and In an oxygen-containing atmosphere, the nitrogen-doped carbon nanotubes embedded with iron-cobalt alloy particles are heated to 160°C~420°C for calcination. After the reaction is complete, the temperature is lowered to room temperature to obtain nitrogen-doped carbon nanotubes embedded with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles. The iron-cobalt oxide-coated iron-cobalt alloy heteroparticles have a core-shell structure, with the core being iron-cobalt alloy and the shell being an iron-cobalt oxide layer.
2. The method for preparing nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles according to claim 1, characterized in that, The ratio of the amount of carbon and nitrogen source, the amount of iron in the iron transition metal salt, the amount of cobalt in the cobalt transition metal salt solution, to the mass of graphene in the graphene oxide aqueous solution is (5mmol~50mmol):(0.5mmol~20mol):(0.5mmol~25mmol):(25mg~100mg).
3. The method for preparing nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles according to claim 1, characterized in that, The concentration of the cobalt transition metal salt solution is 0.3 mol / L to 1 mol / L.
4. The method for preparing nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles according to claim 1, characterized in that, The concentration of the graphene oxide aqueous solution is 0.5 g / L to 2 g / L.
5. The method for preparing nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles according to claim 1, characterized in that, The procedure for removing impurities is as follows: clean with 0.1M~0.5M hydrochloric acid solution.
6. The method for preparing nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles according to claim 1, characterized in that, The inert atmosphere is N2 or Ar, the reducing atmosphere is a mixture of N2 and H2 or a mixture of Ar and H2, and the oxygen-containing atmosphere is air.
7. A nitrogen-doped carbon nanotube with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles embedded in it, characterized in that, The nitrogen-doped carbon nanotubes were prepared using the method described in any one of claims 1 to 6 for preparing iron-cobalt alloy heteroparticles embedded with iron-cobalt oxide.
8. The application of nitrogen-doped carbon nanotubes with iron-cobalt oxide-coated iron-cobalt alloy heteroparticles as described in claim 7 as a catalyst for zinc-air batteries.
Citation Information
Patent Citations
Method for preparing CoFe alloy / graphene oxide / carbon nanotube composite material
CN111450862A
Preparation method and application of carbon nano tube coated with Co-Co3O4 heterogeneous nano particles
CN113725451A